Channel stickiness in the shopping journey for electronics: Evidence from China and South Korea - Song, Hyeasin; Choi, Jeonghye; Kim, Yongseob; Hong, Jeonghan; Kim, Ji Kyung (Jeanne) (Elsevier, 2021)
In today’s era of multichannel marketing, shoppers routinely use multiple channels in a single shopping journey; however, many researchers also report a tendency among shoppers to stay in one channel throughout a shopping journey, a phenomenon we refer to as “channel stickiness”. We investigate which determinants are linked to channel stickiness while accounting for individual characteristics. To this end, we compile and survey a variety of search behavior items. We then compare channel stickiness in two markets with differing levels of e-commerce experience: China (limited) and South Korea (extensive). Our results show that channel stickiness exists for simple products but not for complex ones. Channel stickiness manifests not only in markets in which shoppers have limited e-commerce experience but also in those with extensive experience. Offline search behavior is related to channel perception while online search behavior is related to content usage. Theoretical contributions and managerial implications are also discussed.
Keywords: 53 Ciencias Económicas::5308 Economía general::5308.02 Comportamiento del consumidor; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura; ODS 12 - Producción y consumo responsables